Capitalist-Worker Conflict and Involuntary Unemployment - Osborne, Martin J. (Review of Economic Studies, 1984)
We study a simple model of the determination of the level of employment in which a capitalist decides how many workers to hire, and then bargains over the wage with those whom he hires. If the capitalist hires all the available workers, his position is weak since, in the event of a strike, he is unable to hire strike-breakers; for this reason he chooses to leave some workers ("involuntarily") unemployed. An increase in unemployment benefits which raises the cost of hiring strike-breakers affects the bargaining power of both capitalist and workers; under some conditions it leads to a reduction in unemployment. 1.